2005
DOI: 10.1124/dmd.105.004085
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microsomal Cytochrome P450-Dependent Monooxygenases in the Rat Olfactory Mucosa

Abstract: ABSTRACT:Nasal administration of a drug ensures therapeutic action by rapid systemic absorption and/or the entry of some molecules into the brain through different routes. Many recent studies have pointed out the presence of xenobiotic-metabolizing enzymes in rat olfactory mucosa (OM). Nevertheless, very little is known about the precise identity of isoforms of cytochrome P450 (P450)-dependent monooxygenases (P450) and their metabolic function in this tissue. Therefore, we evaluated mRNA expression of 19 P450 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…Our results showed that the basal mRNA expression and the activity of several phase I and phase II enzymes were of the same order of magnitude or higher in the OM than in the liver. This result is in good agreement with previous observations (Longo et al, 1988;Ben-Arie et al, 1993;Minn et al, 2005). In the present study, we show, for the first time, a significant expression of SULT1C1 mRNA in rat OM.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results showed that the basal mRNA expression and the activity of several phase I and phase II enzymes were of the same order of magnitude or higher in the OM than in the liver. This result is in good agreement with previous observations (Longo et al, 1988;Ben-Arie et al, 1993;Minn et al, 2005). In the present study, we show, for the first time, a significant expression of SULT1C1 mRNA in rat OM.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, although the P450 induction capacities of EQ are well known, inhibitory effects of EQ on P450 activities have also been reported (Stohs and Wu, 1982). Because CZX and POD activities are sustained by several P450s, such as CYP2E1, CYP2G1, 2A3, 1A1, and 1A2 (Minn et al, 2005), it is difficult to determine which enzymes are affected by EQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genes have been identified in the CYP3A subfamily of mammals (for example, five in rat and four in human), but the expression of these genes in nasal tissues has been poorly investigated. A recent study revealed that olfactory tissue of rat expresses a substantial level of CYP3A9 but not CYP3A1 and 3A2 (Minn et al, 2005). Also in the olfactory microsomes of pig, a CYP3A protein band was immunodetected by anti-rat CYP3A1 but the identity of this protein has not been established (Marini et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…In metabolism studies of the CYP substrates by human respiratory mucosa, it was found that ethoxyresorufin was not metabolized, and the metabolisms of both testosterone and loteprednol-etabonate were limited and markedly lower than that in the liver (7). On the contrary, metabolic clearance of testosterone was higher in olfactory mucosa than liver in rat (8). For enzymes such as glutathione transferase, epoxide hydroxylase and rhodanese, Gervasi's study suggested that their activities were comparable or lower than that of human liver, while the nasal UDPglucuronyltransferase activity was undetectable (5).…”
Section: Introductionmentioning
confidence: 84%